Relationship of Food Service to Nutrition Installation with the Level of Satisfaction and Leftover Meals of Inpatients - Andi Purnamasari; Siti Uswatun Hasanah; Siti Masithah; Andi Rahmaniar; Selvia Selvia (Journal La Medihealtico, 2026)
Food service is one of the hospital nutrition services starting from menu planning to food distribution. Minimum Service Standards for food service include punctuality in providing food and food waste ≤ 20%. Based on the results of a survey conducted at La Temmamala Regional Hospital in 2024, the percentage of patient food waste was <20%. This shows that the SPM of the nutrition installation has reached the target, but there are still efforts to maintain and improve. This study aims to examine the relationship between nutrition installation food service and the level of satisfaction and food waste of inpatients at the UPT La Temmamala Regional Hospital, Soppeng Regency. This study uses a quantitative approach with a cross-sectional study design with a sample of 55 inpatients at La Temmamala Regional Hospital. Sampling by purposive sampling was carried out in June 2025. Data were analyzed using the chi-square test. Hospital food service variables for indicators of waiter attitude, punctuality of food distribution and cleanliness of cutlery were rated as good by 55 respondents (100%) for indicators of food menu variety and patient satisfaction variables were rated as good by 54 respondents (98.2%) and less good by 1 respondent (1.8%). There is a relationship between hospital food service and patient satisfaction with a p value of 0.018 and there is no relationship between hospital food service and patient food waste with a p value of 0.291.